2015
DOI: 10.1902/jop.2015.140398
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Relationship Between Metabolic Syndrome and Periodontal Disease Among Japanese Adults Aged ≥70 Years: The Niigata Study

Abstract: These findings support the hypothesis that MetS may be a risk factor for periodontal disease in older Japanese individuals. Additional studies with larger, more diverse populations and more complete information are needed to substantiate the findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 44 publications
1
28
1
2
Order By: Relevance
“…Several studies published subsequent to that review (Thanakun et al 2014;Iwasaki et al 2015;Minagawa et al 2015), but not all (LaMonte et al 2014), also reported significant associations. However, there was considerable variation in the periodontal disease measures and the definitions of MetS used, and few studies were prospective in design.…”
Section: Introductionmentioning
confidence: 92%
“…Several studies published subsequent to that review (Thanakun et al 2014;Iwasaki et al 2015;Minagawa et al 2015), but not all (LaMonte et al 2014), also reported significant associations. However, there was considerable variation in the periodontal disease measures and the definitions of MetS used, and few studies were prospective in design.…”
Section: Introductionmentioning
confidence: 92%
“…, Iwasaki et al. ) have reported that individuals with MetS are more likely to have periodontal disease than those without MetS, suggesting that MetS contributes to the development of periodontal disease. Additionally, two cross‐sectional studies showed that MetS is associated with dental caries (Timonen et al.…”
mentioning
confidence: 99%
“…Oxidative stress may add evidence to elucidate the mechanism of the relationship between systemic health conditions and periodontal disease 16) . Also, changes in environmental factors, eating habits, and life styles that influence obesity may affect the relationship between systemic health conditions and periodontal disease, as a component analysis of each systemic health conditions found abdominal girth in women had the strongest association with periodontal disease 10) .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, obesity was associated with tooth loss among elderly aged 70 years and over 1 [13][14][15] . Longitudinal studies also revealed a causal relationship that people with obesity were more likely to develop periodontal disease 16,17) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation